1989
DOI: 10.1111/j.1346-8138.1989.tb01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Polyarteritis Nodosa: A Clinical and Histopathological Study of 20 Cases

Abstract: Twenty cases diagnosed as cutaneous polyarteritis nodosa (CPN) and confirmed by skin biopsy over the last 17 years were reviewed in our department. Based upon their clinical features, laboratory findings, and long-term observation of the disease course, they were divided into three groups. 1) Group 1 comprised 16 cases which were classified as the mild cutaneous form. The disease was confined to the skin with occasional involvement of peripheral nerves and skeletal muscles of the affected extremity. They gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
8

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 37 publications
3
102
0
8
Order By: Relevance
“…The mainstays of treatment are short courses of nonsteroidal anti-inflammatories or corticosteroids, but immunosuppressive agents can be used to permit corticosteroid tapering. On the basis of data from numerous reports, 40-45% of patients develop a lower-limb neuropathy, more commonly a multifocal neuropathy than a distal polyneuropathy 78,[80][81][82][83][84][85] . Reports of nerve biopsies in patients with cutaneous polyarteritis nodosa are rare, but one revealed vasculitis 86 .…”
Section: Diabetic Lumbosacral Radiculoplexus Neuropathymentioning
confidence: 99%
“…The mainstays of treatment are short courses of nonsteroidal anti-inflammatories or corticosteroids, but immunosuppressive agents can be used to permit corticosteroid tapering. On the basis of data from numerous reports, 40-45% of patients develop a lower-limb neuropathy, more commonly a multifocal neuropathy than a distal polyneuropathy 78,[80][81][82][83][84][85] . Reports of nerve biopsies in patients with cutaneous polyarteritis nodosa are rare, but one revealed vasculitis 86 .…”
Section: Diabetic Lumbosacral Radiculoplexus Neuropathymentioning
confidence: 99%
“…Thus, CPN and PN can be considered to be two independent diseases. However, since rare cases showing progression to PN during long-term follow up have also been reported, 11) careful observation of the course is necessary. Recently, Kawakami et al reported the presence of an antibody against the CPN-specific phosphatidylserine-prothrombin complex.…”
Section: Independence Of Diseasementioning
confidence: 99%
“…Studies of c-PAN report fibrinoid necrosis of the vessel wall and infiltration of lymphocytes and monocytes in the vessel lumen and wall. 7,8 Direct immunofluorescence findings are variable and do not distinguish between c-PAN and systemic PAN. 4,9 While the cause of c-PAN is unknown, it has been associated with group A β-hemolytic Streptococcus, parvovirus B19, human immunodeficiency virus, and hepatitis B infections.…”
Section: Discussionmentioning
confidence: 97%
“…2,9 There are, however, rare cases of progression of c-PAN to systemic PAN. 7 For patients with mild disease, nonsteroidal anti-inflammatory drugs or colchicine may be used. 2,4 Patients with refractory disease, severe cutaneous disease, or extracutaneous involvement require more aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%